Holocene population history of the Sabana de Bogotá region, Northern South America : An assessment of the craniofacial shape variation - Delgado, Miguel Eduardo (2016)
Fil: Delgado, Miguel Eduardo. División Antropología. Facultad de Ciencias Naturales y Museo. Universidad Nacional de La Plata; Argentina